2019
DOI: 10.1177/0010414019830740
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Accountability: An Experimental Investigation of Biases in Evaluations of Governments’ Election Pledges

Abstract: Governments often fulfill election pledges to remain in power; yet, it is unclear how pledge fulfillment and breakage actually affect public support for government. This article explores the tendency for governments to be penalized for unfulfilled pledges more than they are rewarded for fulfilled pledges. In two large-scale highly realistic online survey experiments ( N = 13,000, 10,000), performed at the beginning and middle of a government’s term in office, respondents are presented with a range of (real) el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…All else equal, this suggests that voters consider more statements to be pledges than those normally counted as such in the literature (see, for example, Mansergh and Thomson 2007; Royed 1996; Thomson et al 2017). This might help explain the so-called ‘pledge puzzle’ often highlighted in the literature: that voters in surveys consistently report that governments do not keep their pledges, when, in fact, governments largely do (Müller 2020; Naurin 2011; Naurin, Soroka, and Markwat 2019). If voters consider a larger proportion of party statements to be pledges, governments may – from the point of view of the voters – actually not keep all that many of their promises.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All else equal, this suggests that voters consider more statements to be pledges than those normally counted as such in the literature (see, for example, Mansergh and Thomson 2007; Royed 1996; Thomson et al 2017). This might help explain the so-called ‘pledge puzzle’ often highlighted in the literature: that voters in surveys consistently report that governments do not keep their pledges, when, in fact, governments largely do (Müller 2020; Naurin 2011; Naurin, Soroka, and Markwat 2019). If voters consider a larger proportion of party statements to be pledges, governments may – from the point of view of the voters – actually not keep all that many of their promises.…”
Section: Discussionmentioning
confidence: 98%
“…By building on classic research on election pledges (for example, Mansergh and Thomson 2007; Royed 1996; Thomson 2001), recent literature demonstrates that while voters generally understand pledges quite broadly (Naurin 2011), they tend to focus on the degree of commitment (Dupont et al 2019) and the use of persuasive, value-laden words (Lindgren 2017; Lindgren 2018; Lindgren and Naurin 2017). Another strand of literature convincingly demonstrates that parties do, in fact, keep most of their promises (see also Müller 2020; Thomson et al 2017) and that voters are quite apt to punish and reward parties based on such performances (Matthieß 2020; Naurin, Soroka, and Markwat 2019; see also Thomson 2011). However, apart from these significant contributions, we have a limited understanding of what statement characteristics make voters systematically categorize some as pledges and others as not, and we know relatively little about whether the very same characteristics are used by voters to hold parties and politicians accountable for their pledges.…”
mentioning
confidence: 99%
“…Moreover, increased volatility may result from voters switching parties based on their policy preferences instead of holding on to a particular party out of habit. Overall, there is some empirical work suggesting that policies do matter for citizens' voting decisions (see, for instance, Naurin et al, 2019 who find that government parties are held accountable for breaking pledges, or Dalton, 2019 who show that citizens do vote in line with their policy preferences). While others, such as Achen and Bartels (2017) are more skeptical about citizens' ability and willingness to cast a policyinduced vote.…”
Section: The Black Box Of Politicians' Conception Of Citizens' Party ...mentioning
confidence: 99%
“…The result is that incoming governments are sometimes voted into office on a platform of strong welfare commitment, which can create a tension between the promises made on election day and the ability to deliver afterwards. Given voters' strong negative reactions to broken pledges (Naurin et al 2019), it is not surprising that the mass media has been shown to pay more attention to pledges broken than pledges kept (Duval 2019;Müller 2020).…”
Section: Mass Media Attention and Welfare State Reformmentioning
confidence: 99%